Mass infestation of a rural residential area with millipede larvae: A case report - Jalal Mohammadi; Hossein Faramarzi; Aboozar Soltani (Shiraz University of Medical Sciences, 2019)
The class Diplopoda (the millipedes) is the most abundant and diverse group within the Myriapoda, comprising 15 orders and numerous families. They range in length from very tiny (∼5 mm in Polyxenida) to the longest terrestrial invertebrates (some Spirostreptida being up to 35 cm long) in tropical and subtropical regions. On the 29th September 2018, the residents of Dare Mal (a village of Marvdasht city) were faced with a massive infestation of an unknown larva. Arthropods were transferred to the Entomology Laboratory of Shiraz Health School. The unknown arthropods were identified as millipede larvae belonging to the Polyxenidae family (Polyxenus spp.) Millipede larvae are not of medical importance, but they cause panic among the residents and make them evacuate their homes. The source of their infestation was a leftover farmyard watering near the village. The number of larvae declined sharply and their activity decreased after conducting the control program. This program included physical control as well as spraying of the infested areas with permethrin and diazinon. Activity of larvae abruptly decreased and eventually they were removed from all infested homes.